Integration of Biological Synthesis & Chemical Catalysis: Bio-based Plasticizer trans-Aconitates - Hongbin Hou; Xuenian Huang; Zhiqiang Du; Jian Guo; Min Wang; Guangqiang Xu; Ce Geng; Yunpeng Zhang; Qinggang Wang; Xuefeng Lu (Green Carbon)
Plasticizers are essential to reduce processing difficulties and improve plastic properties. However, petroleum-based phthalate plasticizers, which are mostly used at present, urgently require alternatives due to their confirmed and serious health risks. In this study, the green mass production of trans-aconitic acid was achieved via synthetic biotechnology and microbial fermentation, which was further expanded to multiple application scenarios using chemical esterification, resulting in trans-aconitate plasticizers that are biosafe and environmentally friendly and have high plasticizing efficiency and long-term stability. Different plasticizers with various core structures and alkyl chains were studied to determine their properties as polyvinyl chloride (PVC) plasticizers, and tributyl trans-aconitate displayed the best comprehensive performance with up to 1.24 plasticizing efficiency. The possible PVC plasticization mechanism with synergistic solvent, support, and shielding effects was discussed and summarized. Tributyl trans-aconitate has significant potential to replace traditional PVC plasticizers in general merchandise, food packaging, medicinal materials, and other products, further promoting the development of the high-quality plastic industry with greener technology and safer applications.